On the Development of Marital Law. Issue 2 (4th May 2022) - Aston, Jennifer; Hamilton, Frances
ABSTRACT: This issue of the Journal of Legal History results from a conference organized by Dr Jennifer Aston (Northumbria University) and Dr Frances Hamilton (University of Reading) held virtually at Northumbria University on 20th May 2021. At this event we explored the changing legal and cultural definitions of marriage in any geographical location or jurisdiction across the period c .1450 – present day, utilizing a range of historical, literary, artistic, and cultural perspectives. This issue concentrates on the historical, legal, religious, and cultural perspectives on the development of marital law in England and Wales from the sixteenth to the early twentieth century. The interaction between legal, historical, and religious source materials serves to bring fresh insights, demonstrating how women and Dissenting religious groups experienced the laws relating to marriage and were important actors in driving forward legislative and social change.